Educational transformation in the age of AI: Aframework and implementation path for ai competency for University instructors - Xue Bai; Rosy Binti Talin (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2024)
Higher education is changing dramatically as a result of the quick advancement of artificial intelligence (AI) technologies. This study intends to provide a framework for instructor competency in higher education that is tailored to the AI era and suggest a matching implementation path using the method of literature analysis. After defining AI competency conceptually, the study creates a multifaceted framework with four essential components: knowledge, skills, application, and values. The application dimension concentrates on the use of AI in teaching practice; the knowledge dimension highlights comprehension of the fundamentals of AI; the skills dimension emphasises instructors' proficiency with AI tools; and the values dimension includes a thorough comprehension of AI ethics and social responsibility. The development of an interdisciplinary knowledge system, the development of competence and practical application, and the moral awakening and responsibility are the three main techniques that this study suggests for the implementation path. These tactics aim to improve university instructors' AI competency so they can use AI technology for student learning and development more successfully. The study's findings imply that by systematically putting the measures to assist the transformation of higher education into practice, instructors' AI competency may be effectively raised.